Das Alte Testament - ein Geschichtsbuch? - Loader, James Alfred (Old Testament essays, 2002)
In the context of the colloquium 'Old Testament and Art' as an aspect of the Von Rad Centenary Symposium held at Heidelberg in October 2001, this paper argues that there is a sense in which the Old Testament can - in the German language - be called a single history book, notably narrative as a theological metaphor. It is contended, however, that this may be misleading on other counts. Five arguments are offered from the angles of respectively unity in the absence of codices, the presupposed genre, the implications of the categories of synchrony and diachrony, history as story and the canons of the Old Testament and the Hebrew Bible as 'one' book. It is concluded that neither 'the' final text nor 'the' final canon can be pinpointed since in principle neither can exist. Rather, an aesthetic, creative act is called for in which a decision is made as to which 'final' form is to be used in any particular case. In view of the legitimacy of all among the many 'final forms' preserved by the Jewish and Christian traditions, the variegated nature of these should not only be tolerated, but respected and used imaginatively in contributing to Old Testament studies as an aspect of present-day culture.